Does neoadjuvant chemotherapy increase the survival in patients with locally advanced gastric cancer patients? – A real-world evidence - Murugesan Janarthinakani; Selvaraj Kalaiselvi; Rajamani Priyadarshini; Seshachalam Arun; K Shashidhar; R Krishnakumar; N Manjunath; Sirigeri Roopa; S G Raman (Indian Journal of Medical and Paediatric Oncology)
Background: In locally advanced gastric cancer (LAGC), perioperative chemotherapy has shown to improve the survival to a larger extent compared to surgery alone. In India, the treatment followed for gastric carcinoma widely varies based on the type of health-care provider and treatment access. There is a paucity of data on the role of neoadjuvant chemotherapy on survival among LAGC patients in the Indian context. Aim: The aim of this study was to compare the disease-free survival (DFS) and overall survival (OS) between neoadjuvant and adjuvant chemotherapies among LAGC patients. Subjects and Methods: This was a retrospective cohort study involving clinical record review of LAGC patients enrolled between 2015 and 2017 from four tertiary cancer centers in South India. The date for the following events, namely diagnosis, recurrence, death, and last day of visit, was extracted in a mobile-based open-access tool. The median duration of OS and DFS between the neoadjuvant and adjuvant groups was compared using Kaplan–Meier survival curves. Results: Of the 137 patients, 70 (51%) had received neoadjuvant chemotherapy followed by surgery and 67 (49%) had adjuvant chemotherapy following the surgery. The mean (standard deviation) age of participants was 55.4 (11.4) years. Seventy-eight percent of the patients were diagnosed at Stage 3 or 4. Regional lymph nodes were involved in 83.9%. The median duration of follow-up was 15 months. The OS in the neoadjuvant and adjuvant groups was 18.6 months and 8.3 months, respectively. Nonregional lymph node involvement and adjacent organ involvement had independently increased the risk of death. Conclusion: Among LAGC patients, the neoadjuvant chemotherapy indicated a better median and DFS compared to the adjuvant group. However, these findings were statistically not significant. The current study has contributed an important finding to the existing evidences of clinical practice in an Indian setting. Further large-scale studies are required to validate the promising trend of using neoadjuvant chemotherapy in LAGC.